Pengaruh Pengetahuan Akuntansi dan Tingkat Pendidikan Terhadap Laporan Keuangan di Sekolah Menengah Pertama Swasta Wilayah Subrayon 05 Kabupaten Bekasi - Siti Syafa'at; Dany Prio Hutomo (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
Developing countries are countries that value education, but in improving the quality of education services there are gaps in accounting information, such as financial reports which need attention and improvement in their services. The purpose of this study was to determine whether accounting knowledge and education level affect the quality of financial reporting at private secondary schools in Soubrayon 05 Bekasi Regency. This research is quantitative, with a population of twenty-nine schools in the region and sample data taken using a questionnaire according to purposive sampling technique with a total of 51 people. The data analysis technique used is multiple regression analysis, classical assumptions and hypotheses. The results of this study indicate that all are valid and reliable, with the accounting knowledge variable showing a significance value of 0.014 below 0.05, and the education level variable showing a significance value of 0.006 below 0.05, which means each is accepted and shows there is an influence on the quality of financial statements. The simultaneous test results also show a significance value of 0.011 below 0.05 where Accounting Knowledge and Education Level together have a significant effect on the Quality of Financial Statements.